ULTRASONOGRAPHIC VS VERNIER CALIPERIC EVALUATION OF TESTES AND ACCESSORY GLANDS IN ONGOLE (BOS INDICUS) BULLS - SRINIVAS, MANDA; NAIDU, K S; SREENU, MAKKENA; RAO, K BABU; SRILATHA, CH (The Indian Journal of Animal Reproduction, 2023)
Breeding soundness evaluation was performed on 8 Ongole bulls aged between 3 to 5 years. The testicularbiometry was compared between ultrasonography verses vernier measurements and trans-rectal ultrasonographywas performed to evaluate the accessory sex glands. The mean body condition score was 6.63 ± 0.18. The overallmean scrotal circumference was 34.63 ± 0.21 cm and, it had a significant positive correlation with biometry ofscrotum and testes, testicular volume, testicular weight and ejaculate volume (P
Keywords: Ongole bulls; Breeding soundness; Ultrasonography; Testicular biometry; Accessory sex glands